Uwagi o bezpochówkowych kurhanach kultury pomorskiej na obszarze Pojezierza Kaszubskiego - Janiak, Radosław (Zeszyty Wiejskie, 2016)
Along with typical mounds, the barrow cemeteries of the Pomeranian culture that were common in the area of the Kaszuby Lake District also yielded stone structures containing no burials. Their diameters were most often smaller than in barrows covering a centrally placed burial. Moreover, the discussed structures were typically not surrounded by a stone circle marking the perimeter. In terms of form, however, they resembled barrows: they were circular in plan and had mounds, and they undoubtedly should be regarded as an integral part of a given barrow necropolis. The structures were built of stones of selected size. Larger blocks were used for the base, while the mound was raised from smaller pieces. Burial-less barrows are interpreted as structures having a symbolic meaning. A good example is site 2 at Nowa Sikorska Huta in Stężyca commune, where structures of the discussed type occupied one of the two identified zones of stone structures occurrence. In the second zone they occurred along with barrows containing burials. A similar situation was recorded in the cemetery at Żaków, site 3, in Sulęczyno commune. In this case, the structures with no burials co-occurred with typical barrows in the lowermost part of the cemetery, at the foot of a moraine hill. In the higher parts (the slope and edge of the hill), however, the discussed structures were predominant.